Dopamine and opioid neurotransmission in behavioral addictions: a comparative PET study in pathological gambling and binge eating - Majuri, Joonas (fi=Turun yliopisto|en=University of Turku|, 2016)
Although behavioral addictions share many clinical features with drug addictions, they show strikingly large variation in their behavioral phenotypes (such as in uncontrollable gambling or eating). Neurotransmitter function in behavioral addictions is poorly understood but has important implications in understanding its relationship with substance use disorders and underlying mechanisms of therapeutic efficacy. Here, we compare opioid and dopamine function between two behavioral addiction phenotypes: pathological gambling (PG) and binge eating disorder (BED). Thirty nine participants (15 PG, 7 BED and 17 controls) were scanned with [11C]carfentanil and [18F]fluorodopa positron emission tomography using a high-resolution scanner. Binding potentials relative to non-displaceable binding (BPND) for [11C]carfentanil and influx rate constant (Ki) values for [18F]fluorodopa were analyzed with region-ofinterest and whole-brain voxel-by-voxel analyses. BED subjects showed widespread reductions in [11C]carfentanil BPND in multiple subcortical and cortical brain regions and in striatal [18F]fluorodopa Ki compared with controls. In PG patients,[11C]carfentanil BPND was reduced in the anterior cingulate with no differences in [18F]fluorodopa Ki compared with controls. In the nucleus accumbens, a key region involved in reward processing, [11C]Carfentanil BPND was 30-34% lower and [18F]fluorodopa Ki was 20% lower in BED compared with PG and controls (p<0.002). BED and PG are thus dissociable as a function of dopaminergic and opioidergic neurotransmission. Compared with PG, BED patients show widespread losses of mu-opioid receptor availability together with presynaptic dopaminergic defects. These findings highlight the heterogeneity underlying the subtypes of addiction and indicate differential mechanisms in the expression of pathological behaviors and responses to treatment.

Toiminnalliset riippuvuudet ovat sairauksia, joille luonteenomaista on pakonomainen välittömän palkkion tavoittelu. Kansainvälisessä kirjallisuudessa on esitetty, että riippuvuussairauden taustalla saattaisivat vaikuttaa samanlaiset muutokset keskushermoston välittäjäaineiden toiminnassa riippumatta riippuvuuden kohteesta. Tämän syventävän työn tarkoituksena on tutkia kahden eri toiminnallisen riippuvuuden, rahapeliriippuvuuden ja ahmintahäiriön, välisiä eroja ja yhtäläisyyksiä keskushermoston hermovälittäjäaineiden esiintymisessä. 15 rahapeliriippuvaisen, seitsemän ahmintahäiriöisen sekä 17 terveen verrokin aivot kuvattiin kahdesti positroniemissiotomografialla ja kerran rakenteellisella magneettikuvauksella. Merkkiaineena positroniemissiotomografiassa käytettiin μ- opioidireseptoriin sitoutuvaa [11C]karfentaniilia ja dopamiinin muodostumista kuvaavaa [18F]fluorodopaa. Tilastollisessa analyysissa peliriippuvaisia ja ahmintahäiriöisiä verrattiin sekä verrokkiryhmään että toisiinsa. Tulokset laskettiin tavanomaisilla tilastomenetelmillä ja aivojen tilavuusyksiköihin perustuvilla menetelmillä. Ahmintahäiriöisillä [11C]karfentaniilin sitoutuminen oli alentunut laajasti aivojen eri osissa, muun muassa palkkiojärjestelmään keskeisesti liittyvillä aivoalueilla. Peliriippuvaisilla [11C]karfentaniilin sitoutuminen oli alentunut vain pihtipoimun etuosissa. [18F]fluorodopan sitoutuminen oli ahmintahäiriöisillä alentunut aivojen palkkiojärjestelmän keskeisellä alueella accumbens-tumakkeessa. Vastaavaa sitoutumisen alenemista ei havaittu rahapeliriippuvaisilla. Sitoutumisen voimakkuus ei riippunut koehenkilöiden iästä, sukupuolesta, painoindeksistä eikä tupakoinnista. Löydökset osoittavat, että toiminnalliset riippuvuudet ovat neurobiologisesti erilaisia sairauksia.
Dopamiinin ja opioidin neurotransmissio toiminnallisissa riippuvuuksissa: peliriippuvuuden ja ahmintahäiriön vertaileva PET-tutkimus